Research-based learning (RBL) based on digital learning environment (DLE) in the context of TPACK proficiency among prospective mathematics teachers viewed from creative thinking ability: A quasi-experimental study - Puput Suriyah; Sujiran; Dwi Erna Novianti; Ali Noeruddin; Dina Mariana (Proceeding International Conference on Digital Education and Social Science, 2024)
This article presents an experimental study conducted to examine the impact of a research-based learning (RBL) approach based on a digital learning environment (DLE) on the Technological Pedagogical Content Knowledge (TPACK) proficiency and creative thinking abilities of prospective mathematics teachers. The study aims to prepare these teachers for the Society 5.0 era and support the government's educational initiatives. The researchers integrated a DLE consisting of an integrated website with a Learning Management System (LMS) Moodle, which included e-modules, quizzes, and other resources. The study also emphasizes the importance of character development and the need for teachers to possess strong TPACK knowledge and creative thinking skills. The TPACK framework, which encompasses pedagogical content knowledge, technological pedagogical knowledge, technological content knowledge, and technological pedagogical content knowledge, is considered crucial for effective technology integration in teaching. The researchers conducted a quasi-experimental study using a 3 x 3 factorial design to investigate the influence of different instructional models on TPACK capabilities among students at different stages of creative thinking skills. The study collected data through documentation, observation, interviews, and tests. The data were analyzed using analysis of variance (ANOVA) and post-hoc multiple comparisons. The findings of the study contribute to the advancement of education and align with the goals of the Merdeka Belajar-Kampus Merdeka (MBKM) initiative, emphasizing innovation, collaboration, and sustainable practices in education.